2022
DOI: 10.1111/eci.13904
|View full text |Cite
|
Sign up to set email alerts
|

The impact of inter‐clinician electronic consultation in patients diagnosed with atrial fibrillation in primary care

Abstract: Background An early diagnosis and early initiation of oral anticoagulants (OAC) are main determinants for outcomes in patients with atrial fibrillation (AF). Inter‐clinician electronic consultations (e‐consultations) program for the general practitioner referrals to cardiologist may improve health care access by reducing the elapsed time for cardiology care. Objective To evaluate the effect of a reduced elapsed time to care after a inter‐clinician e‐consultations program implementation (2013–2019) in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We have previously published our experience using a universal e‐consultation programme between PCPs and CDs for over 10 years, which has shown promising results in managing referrals. Our study has demonstrated that this programme is associated with a reduction in waiting lists and better health outcomes, for all patients 4,14 including those with a previous diagnosis of cardiac disease such as HF 23 and AF 24 . In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old 25 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We have previously published our experience using a universal e‐consultation programme between PCPs and CDs for over 10 years, which has shown promising results in managing referrals. Our study has demonstrated that this programme is associated with a reduction in waiting lists and better health outcomes, for all patients 4,14 including those with a previous diagnosis of cardiac disease such as HF 23 and AF 24 . In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old 25 .…”
Section: Discussionmentioning
confidence: 68%
“…Our study has demonstrated that this programme is associated with a reduction in waiting lists and better health outcomes, for all patients 4,14 including those with a previous diagnosis of cardiac disease such as HF 23 and AF. 24 In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old. 25 Our study has also highlighted that clinician-to-clinician programmes, such as e-consultation, can enhance healthcare equity and quality, which is especially important for vulnerable patients, including women.…”
Section: Allmentioning
confidence: 99%
“…3,6 However, data evaluating the effectiveness of e-consultation on clinical outcomes have been scarce. 6 In the present issue, Mazón-Ramos and colleagues 7 report the first study to show the prognostic benefit of e-consultation in AF management in the primary care setting. In this nonrandomized before-after design study, the authors collected data on 10,488 patients with newly diagnosed AF who were referred by a pool of 301 primary care physicians to cardiologists between 2010 and 2019.…”
Section: Improving Atrial Fibrillation Outcomes Through Interclinicia...mentioning
confidence: 87%
“…Several publications have described our experience using this care model in our health care area, demonstrating that the use of an universal electronic consultation between PCPs and cardiologists as the first step to attend to referrals is associated with a reduction in the elapsed time to care and better health care outcomes [8,11] particularly in high risk patients such as those with HF and previous hospitalization for a worsening HF event [9,10,25].…”
Section: Discussionmentioning
confidence: 99%